Synthesis of heterocycles from arylacetonitriles: Powerful tools for medicinal chemists. Issue 27 (5th July 2017) - Lindsay-Scott, Peter J.; Gallagher, Peter T.
Graphical abstract: Highlights: Arylacetonitriles can engage in a variety of synthetic transformations. Many heterocyclic scaffolds can be synthesised from arylacetonitriles. These heterocycles are useful for medicinal chemistry applications. Several disease areas have been investigated using this synthetic methodology. Abstract: Arylacetonitriles are versatile building blocks for the construction of heterocyclic scaffolds in medicinal chemistry. These intermediates are able to engage in a variety of synthetic transformations, giving rise to diverse biologically active structures. This digest focuses on recent applications of this synthetic methodology by drug discovery teams across several disease areas, with an emphasis on different reaction types.